Screening of ethanol-tolerant fusants of Saccharomyces cerevisiae and Pichia stipitis from protoplast fusion - Fawzia Jassim Shalsh; Noor Azlina Ibrahim; Mohammed Arifullah (Maxwell Scientific Organization, 2016)
Bioethanol is gaining increasing attention as a clean and renewable fuel because of its major environmental beneﬁts. Efﬁcient bioethanol fermentation requires the selection of superior strains that are capable of ethanol stress tolerance. Yeast can produce ethanol, thereby reﬂecting its intrinsic ability to tolerate ethanol. This study focuses on ethanol tolerance enhancement of Saccharomyces cerevisiae for ethanol production improvement through protoplast fusion. S cerevisiae and P. stipitis fusants (ATCC 58785), which can ferment xylose, were isolated. The ability of these isolates tolerate ethanol was investigated by allowing the strains to grow in different ethanol concentrations. Results showed the ability of the fusantsto have an average tolerance to ethanol when compared with the parent strains and fermented glucose in the presence of 6% ethanol. By contrast, the parent strains S. cerevisiae and P. stipitis showed ethanol tolerances of 8 and 4%, respectively. Fusant formation was conﬁrmed by the increased DNA content. This outcome suggests that multiple fusions had occurred and the genetic stability of fusants indicates that F24 and F18 are genetically stable and suitable for industrial production.